“It is Sad that Lackeys Have Power...” (Unknown Letters from the Archive of B.V. Tomashevsky) - O. V. Nikitin (Научный диалог)
The article is devoted to the epistolary heritage of the legendary philologist of the XX century — Professor Boris Viktorovich Tomashevsky (1890—1957) and his relations with the leading scientists in the context of historical, literary, linguistic and ideological polemics mainly of the 1930s and 1950s. The paper emphasizes the contribution of the scientist to the development of world science in the era of cultural upheavals. Special attention is paid to the publications of unknown epistles to B.V. Tomashevsky by domestic and foreign philologists: I.L. Andronikov, G.O. Vinokur, D.S. Likhachev, A. A. Reformatsky, B. Unbegaun, M. Vasmer, R. O. Jakobson. The published letters describe the situation in science of that period: they show the difficulties in working on the publication of Pushkin’s “Complete Works”, reveal the polemics around controversial issues of the theory and practice of the text, express the attitude of cor-respondents to the facts of ideological pressing on science, describe the difficulties of wartime, etc. B. V. Tomashevsky’s epistolary is also considered in the context of the role of Soviet linguistic personality in creating scientific tradition. The relevance of the study is due to the use of archival mate-rials in the paradigm of the humanities to clarify poorly studied facts of the 1930s and 1950s.